(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2024)
Background. The aftermath of the war in Ukraine highlights the harmful effects of stressful situations on both the local population and pharmaceutical professionals. Undertaking preventative measures to maintain the mental well-being of the population, while also establishing selfhelp mechanisms in the workplace for issues related to mental health, will improve the quality of pharmaceutical care in the field of drug sales and curb early professional burnout among pharmacists. The purpose of this study is to perform a comparative analysis of educational and professional programmes in the specialty of 226 Pharmacy, Industrial Pharmacy, with the objective of assessing the level of masters of pharmacy training in facilitating their own mental health. The study will further investigate the incorporation of relevant course components in the curriculum. Methods. To attain the research goal, the authors utilized scientific literature, worldwide documents, official websites of academic Hiher education institutions, educational and professional programmes within the specialty of 226 Pharmacy, Industrial Pharmacy employing comparative analysis, systematisation, and generalisation methods. Results. The article presents a comparative analysis of educational and professional courses for Masters of Pharmacy in the 226 Pharmacy, Industrial Pharmacy Speciality. The documents and research findings of international scholars have been systematised to tackle the training of pharmacists to handle stressful situations and emergencies. Conclusions. The research conducted indicates that self-help in the workplace of pharmacists is a prevalent global practice, and it has been incorporated into specialised mental health education programmes in various countries. The authors believe that incorporating the best educational practices from Masters of Pharmacy training to include self help for mental health issues in the workplace into national educational and professional programmes in the 226 Pharmacy, Industrial Pharmacy specialty shows promise.